Participants' explanatory model of being overweight and their experiences of 2 weight loss interventions. - Ahern, A; Boyland, E; Jebb, SA; Cohn, SR (2013)
PURPOSE: We explored participants' accounts of weight loss interventions to illuminate the reasons behind the greater weight loss observed among those attending a commercial program compared with those receiving standard care in a recent large-scale trial. We further wanted to examine how participants' general explanatory model of being overweight related to the 2 different interventions. METHODS: Our study was based on thematic analysis of semistructured telephone interviews with a purposeful sample of 16 female participants from the UK center of a randomized controlled trial of weight loss in primary care. RESULTS: The commercial provider delivered weight management in a nonmedical context, which mirrors how participants regard being overweight. Participants felt they needed support and motivation rather than education, and valued the ease of access and frequent contact the commercial provider offered. Some participants preferred individual level support with their primary care clinician, and all were positive about the opportunity to access support through the primary care setting. CONCLUSIONS: Primary care referral to a commercial weight loss program for people who do not require specific clinical care appears to be in accord with their general explanatory model about being overweight, offering motivation and support to lose weight outside a strictly medical context. This approach may not be effective or acceptable for everyone, however, and there are likely to be considerable variations in the explanatory models held. Findings support the argument that a range of evidence-based options for weight management should be available in primary care.